Vitamin D and inflammation - Zuljasri Albar (Indonesia Rheumatology Association, 2018)
The discovery that most body cells and tissues have vitamin D receptors and that some of them have the enzymatic machinery to convert the circulating form of vitamin D (25-hydroxyvitamin D) into the active form (1,25- dihydroxyvitamin D/1,25(OH)2D3 ) gave a new insight about the function of this vitamin. In the course of time, more and more evidences showed that a low vitamin D level leads to the occurrence or recurrence of cardiovascular diseases, type II diabetes mellitus (DM), cell dedifferentiation (oncogenesis), and immune derangement (autoimmune diseases such as lupus, type I DM, rheumatoid arthritis, and multiple sclerosis). Most researchers have agreed that a minimum 25(OH)D3 serum level of about 30 ng/ml or more is necessary for favorable calcium absorption and good health. Until proven otherwise, the balance of the research clearly indicates that oral supplementation in the range of 1,000 IU/day for infants, 2,000 IU/day for children, and 4,000 IU/day for adults is safe and reasonable to meet physiologic requirements, to promote optimal health, and to reduce the risk of several serious diseases.